2024
DOI: 10.3390/info15010033
|View full text |Cite
|
Sign up to set email alerts
|

Higher Education Students’ Task Motivation in the Generative Artificial Intelligence Context: The Case of ChatGPT

Mohammad Hmoud,
Hadeel Swaity,
Nardin Hamad
et al.

Abstract: Artificial intelligence has been attracting the attention of educational researchers recently, especially ChatGPT as a generative artificial intelligence tool. The context of generative artificial intelligence could impact different aspects of students’ learning, such as the motivational aspect. The present research intended to investigate the characteristics of students’ task motivation in the artificial intelligence context, specifically in the ChatGPT context. The researchers interviewed 15 students about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…As the student's comment suggests, ChatGPT increased their motivation by providing sufficient assistance. Hmoud et al (2024) supported this, arguing that students had a stronger sense of value in the learning processes after gaining effective support from ChatGPT to augment their task completion weaknesses. Additionally, ChatGPT's usefulness enhances learners' sense of control over the learning process and increases their joy (Qu & Wu, 2024), and self-confidence (Hmoud et al, 2024).…”
Section: Chatgpt's Positive and Negative Motivational Impacts On L2 L...mentioning
confidence: 85%
See 1 more Smart Citation
“…As the student's comment suggests, ChatGPT increased their motivation by providing sufficient assistance. Hmoud et al (2024) supported this, arguing that students had a stronger sense of value in the learning processes after gaining effective support from ChatGPT to augment their task completion weaknesses. Additionally, ChatGPT's usefulness enhances learners' sense of control over the learning process and increases their joy (Qu & Wu, 2024), and self-confidence (Hmoud et al, 2024).…”
Section: Chatgpt's Positive and Negative Motivational Impacts On L2 L...mentioning
confidence: 85%
“…Hmoud et al (2024) supported this, arguing that students had a stronger sense of value in the learning processes after gaining effective support from ChatGPT to augment their task completion weaknesses. Additionally, ChatGPT's usefulness enhances learners' sense of control over the learning process and increases their joy (Qu & Wu, 2024), and self-confidence (Hmoud et al, 2024). In summary, obtaining individualized and effective support from ChatGPT enhances learners' sense of control over their learning, leading to increased motivation.…”
Section: Chatgpt's Positive and Negative Motivational Impacts On L2 L...mentioning
confidence: 85%
“…Students were, on average, 19 years old. The students who participated in the in-depth interviews (14) were all Black African by the study's design, predominantly male (9 out of 14 participants) and came from varied socio-economic backgrounds.…”
Section: Samplementioning
confidence: 99%
“…Some researchers [12] focus on the positive role that generative AI can play in higher education, for example, aiding in managing large classes and online learning. Other researchers focus on how generative AI will impact assessment [13], how it can be used to promote student learning and motivation [14] and which frameworks to use when integrating Chatbots into teaching and learning [15]. Most articles conclude that we need more research and guidelines on using generative AI in higher education [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that ChatGPT can have several positive impacts on students' learning experiences. Recent studies (Pesovski et al, 2024;Hmoud et al, 2024) found that students exhibited increased motivation and engagement when interacting with the AI. The conversational nature of ChatGPT makes learning more interactive and personalized, capturing students' interest and encouraging active participation.…”
Section: Introductionmentioning
confidence: 99%